Workload and work motivation relationships with nursing performance - Amalia Kinanti, Rizky; Linggardini, Kris (Proceedings Series on Health & Medical Sciences, 2020)
Some provinces in Indonesia have been conducted by the directorate of health care service in 2004 with WHO, as a result that 70,4% of nurses have never had training, 39,8% of nurses at the hospital performed non nursing duties, 47,4% of non essential written duties. No specialized supervision and evaluation of nurses. According to interviews with some nurses in the Purbalingga Regency said the nurses’ workload was high because of the extra work off-duty and the function of a nurse. The objective for knowing the relationship of workload and work motivation with a nurse’s performance. This type of research is quantitative using a descriptive design correlation with a sectional cross. The population in this study is all the nurses in the Kutasari medikal center, the Purbalingga Center, the Kalikajar Center and the Kaligondang medical center in Purbalingga District. The sampling technique used is total sampling that is 33 respondents. Analysis used statistics in the chi square. Statistics in this study consist of frequency workload, work motivation and nurse performance. From the results of data processing, it is found that there is a relationship between workload and nurses’ performance with a p-value of 0.017 <0.05. And there’s no connection between work motivation with nurse performance with p-value of 0.422 >0.05. There is a correlation between workload and nurse performance and no correlation between work motivation and nurse performance.